(untitled) (Contextos: Estudios de Humanidades y Ciencias Sociales, 2017)
This research, which is under development, seeks to understand the ideas around the concepts of normality and difference expressed by students in the last two years of the English teaching program at Universidad Metropolitana de Ciencias de la Educación (UMCE), future teachers who in their professional work will exert a major influence on the subjectivities of students and their possibilities of learning. The dimensions under the scope of our analysis are those of gender, ethnicity and social class. In this article, preliminary reflections on the analysis of the results of the validation of the methodology applied are shared.